Preparation & characterization of co/zn catalyst, SBA-15 supported for fisher tropsch synthesis - Mohammad Fairuz, Mohammad Naffekyudin (2010)
The influence of promoter (Zn) and effect of cobalt loading on the physiochemical and catalytic properties of mesaporous silica Co/SBA-15 catalysts for the Fischer-Tropsch (FT) synthesis was investigated. SBA-15 was synthesized as support. The mesoporous silica Co-Zn/SBA-15 catalysts were prepared by incipient wetness impregnation method. Cobalt nitrate and zinc nitrate were used as sources of metal that introduced onto support with same zinc loading (20wt%) and different cobalt loading (5 wt%,10wt%,15wt%).The characterization of catalysts was performed by using Fourier transform Infrared (FTIR) and Scanning Electron Microscopy (SEM). The results for FTIR were identification of Si-O-Zn and Si-O-Co functional group because of the present of zinc or cobalt onto silica SBA-15 support. Besides that, the identification of metal inside SBA-15 was determined by comparing the pure SBA-15 with the incorporated metal on SBA-15. For SEM analysis, the image shows that the rope like domain aggregated to wheat like microstructure. Incorporation of Co and Zn did not change the morphology of the support. For this research, the characterization of the catalyst by selecting Zn as promoter have quiet similar characterization with noble metal that already investigate.